(untitled) (Proceeding of Saizu International Conference on Transdisciplinary Religious Studies, 2023)
The diverse abilities of students require the use of appropriate learning models and methods in the biology learning process. This research aims to find out how the effect of problem based learning (PBL) based on the talk show method on critical thinking skills is carried out at the X MIPA class level at MA Negeri 2 Kab. Tasikmalaya. The research method is a quasi-experimental type with a non-equivalent group design. Sampling used a random sampling technique, with class X MIPA 5 as the experimental class and X MIPA 7 as the control class. The results of the study for the analysis of the influence obtained data on the asymp sig value. (2 tailed) of 0.000 <0.05 with the hypothesis decision being accepted. The average analysis of students’ critical thinking skills was 75.00 for the experimental class and 57.8 for the control class. The calculation of the percentage of the influence of models and methods on critical thinking skills is 94% with the high category in the experimental class and the control class, with an average score at intervals of 53-82 with a high category and fulfilling the minimum completeness criteria (KKM). Based on the results of the study it was concluded that the use of the problem based learning (PBL) model based on the talk show method had a positive influence on students’ critical thinking skills on environmental pollution material.